2001
DOI: 10.1093/brain/124.3.617
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging in patients with epilepsy and malformations of cortical development

Abstract: Malformations of cortical development (MCD) are a common cause of epilepsy. Studies of structural MRIs and PET data in patients with MCD have found widespread changes outside the visually identified lesions. The aim of this study was to investigate diffusion changes interictally in patients with MCD and to test the hypothesis that MCD would be associated with widespread abnormalities of diffusion. We used diffusion tensor imaging (DTI) and statistical parametric mapping (SPM) to compare objectively tissue orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
196
1
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(217 citation statements)
references
References 46 publications
11
196
1
5
Order By: Relevance
“…Most previous voxel-based DTI reports (Barnea-Goraly et al, 2003;Eriksson et al, 2001;Foong et al, 2002;Rugg-Gunn et al, 2001) have used a method similar to the one used for the voxel-based analysis of the structural scans called "voxel based morphometry".…”
Section: Voxel-based Analysis: Asymmetry Of Diffusion Tensormentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous voxel-based DTI reports (Barnea-Goraly et al, 2003;Eriksson et al, 2001;Foong et al, 2002;Rugg-Gunn et al, 2001) have used a method similar to the one used for the voxel-based analysis of the structural scans called "voxel based morphometry".…”
Section: Voxel-based Analysis: Asymmetry Of Diffusion Tensormentioning
confidence: 99%
“…In the analysis of gray matter, each gyrus and sulcus can be mapped to the corresponding template structure based only on the signal intensity obtained from T1-or T2-weighted images. However, structural MR images, which have been generally used for previous voxel-based studies of fractional anisotropy (Barnea-Goraly et al, 2003;Burns et al, 2003;Eriksson et al, 2001;Foong et al, 2002;Rugg-Gunn et al, 2001), do not include information essential for finding anatomical correspondence of the white matter structures (namely, fiber tract's orientation and organization) and thus might not be appropriate for finding precise anatomical correspondence in DT-MRI. This is why we used a more complex registration approach that utilizes multiple channel tensor information to match anatomical correspondence between subjects and between hemispheres instead of using fractional anisotropy or T2-weighted images, even for the analysis of fractional anisotropy.…”
Section: Voxel-based Analysis Of Asymmetry Of Diffusion Tensor In Whimentioning
confidence: 99%
“…Prior studies have shown reduced white matter in cerebral hemispheres, often with reduced diffusion (4,11,12). Lim et al presented a case with bilateral schizencephaly with radiating gray matter signal extending from the ventricle to the cortex; DTI was also used in that report (10).…”
Section: B a Cmentioning
confidence: 99%
“…Abnormal diffusion anisotropy has also been found beyond the visualized limits of MCD. 13 The fact that Leite and her colleagues found abnormal MR spectroscopy profiles even in the contralateral hemisphere is important but not surprising. The most important observation from their study is that one needs to be very cautious when using the contralateral brain as an internal control in patients with focal epilepsy.…”
mentioning
confidence: 98%